Gaya Hidup Komunitas Dance Cover Korea - Muhammad Raynaldi Arief; Neni Yulianita (Bandung Conference Series: Public Relations, 2022)
Abstrack. The popularity of K-Pop in Indonesia has caused many K-Pop fan communities to emerge, one of which is the Korean Dance Cover. Korean Dance Cover Community is a community or association of people who like South Korean culture. The activities of the Korean Dance Cover community focus on the art of dance. The purpose of this study is to determine the motives, actions and meanings of the Korean Dance Cover community lifestyle in Bandung. While the benefits of this research are expected to bring benefits to the development of communication science, especially in the field of Public Relations.This study uses a qualitative method with a phenomenological approach. The research core informants consisted of 10 people who were members of the Korean Dance Cover community in Bandung. Data collection techniques were carried out by means of observation and indepth interviews. This study uses a phenomenological research data analysis technique according to Alfred Schutz. Abstrak. Kepopuleran K-Pop di Indonesia menyebabkan banyak bermunculan komunitas penggemar K-Pop, salah satunya Dance Cover Korea. Komunitas Dance Cover Korea merupakan komunitas atau perkumpulan orang-orang yang menyukai budaya Korea Selatan. Kegiatan dari komunitas Dance Cover Korea ini fokus pada bidang seni tari. Tujuan dari penelitian ini yaitu untuk mengetahui motif, tindakan dan makna gaya hidup komunitas Dance Cover Korea di Bandung. Sedangkan manfaat dari penelitian ini diharapkan mampu mendatangkan manfaat bagi pengembangan ilmu komunikasi khususnya pada bidang Public Relations. Penelitian ini menggunakan metode kualitatif dengan pendekatan secara fenomenologi. Informan inti penelitian terdiri dari 10 orang yang merupakan anggota komunitas Dance Cover Korea di Bandung. Teknik pengumpulan data dilakukan dengan cara observasi dan wawancara mendalam. Penelitian ini menggunakan Teknik analisis data penelitian fenomenologi menurut Alfred Schutz.